The Interactional Bind of "Just [Do X]". Issue 4 (2nd October 2017) - Holmes, Edward J. B.; Toerien, Merran; Jackson, Clare
ABSTRACT: This article examines the use of just -formulated advisings in ordinary, naturally occurring sequences of unsolicited advice giving when produced in response to troubles-tellings. Drawing on two examples from our broader collection, we demonstrate that such advisings are employed in response to advice resistance and function to minimize proposed courses of future action, attenuating their imposing nature. We show they place an interactional bind upon advice recipients that contributes toward further resistance. This article explicates this bind and its categorial, epistemic, and moral implications. Data are in American and British English.